2011
DOI: 10.1186/1476-511x-10-138
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary n-6 and n-3 fatty acids and arachidonic acid compositions in plasma and erythrocytes in young and elderly Japanese volunteers

Abstract: BackgroundWe reported that the compositions of arachidonic acid (ARA) in erythrocytes and plasma phospholipids (PL) in the elderly were lower than those in the young, though the ARA intake was nearly identical.ObjectiveWe further analyzed data in four study groups with different ages and sexes, and determined that the blood ARA levels were affected by the kinds of dietary fatty acids ingested.MethodsOne hundred and four healthy young and elderly volunteers were recruited. Dietary records together with photogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 23 publications
2
16
1
Order By: Relevance
“…In a Danish case-control study, adipose tissue content ARA was positively associated with the risk for myocardial infarction [20]. On the other hand, some studies do not support the association of ARA with the incidence of inflammatory diseases [21] and suggest an anti-inflammatory effect of lipoxin derived from ARA [22]. The results of this study showing an increase trend of serum ARA concentrations among Japanese may suggest the secular change of eicosanoids derived from ARA.…”
Section: Discussionmentioning
confidence: 76%
“…In a Danish case-control study, adipose tissue content ARA was positively associated with the risk for myocardial infarction [20]. On the other hand, some studies do not support the association of ARA with the incidence of inflammatory diseases [21] and suggest an anti-inflammatory effect of lipoxin derived from ARA [22]. The results of this study showing an increase trend of serum ARA concentrations among Japanese may suggest the secular change of eicosanoids derived from ARA.…”
Section: Discussionmentioning
confidence: 76%
“…In other studies, there was no significant difference in P300 components between men and women in Japanese elderly 26 . As for blood ARA level, there was no significant difference in elderly men and women 27 . These data suggest that there may be little effect of gender also in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…Regardless of the timing of maternal blood sampling, the PUFA level in maternal erythrocytes could predict the umbilical cord blood erythrocyte PUFA level from the viewpoint of individual differences within a population group. However, when attempting to predict erythrocyte PUFA levels in umbilical cord blood, it becomes an indispensable condition that the dietary habits from the period of drawing blood to the time of childbirth remain essentially the same, because it is known that EPA and DHA levels in blood tend to be affected by dietary fish intake [11,13,14]. When we predict PUFA levels in infants using maternal blood sampled during pregnancy, but not at the time of delivery, previous studies reported that PUFA levels in erythrocytes were better than plasma PUFA levels [20].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that the erythrocyte DHA composition in Japanese people was 7.0% in less than 35-year-old males [8], 6.4% in 20 to 60-year-old women [9], and 7.9% in middle-aged men and women [10]. It has been widely shown that there is an association between dietary n-3 PUFA intake and n-3 PUFA composition in blood [11,12,13,14]. Lands [15] showed a positive correlation of the percentage of n-3 fatty acids in blood 20- and 22-carbon PUFAs and the daily menu balance values determined by the balance of n-6 and n-3 fatty acids (en%) in food; the daily menu balance value of traditional Japanese foods was highly positioned, next to that of Greenland.…”
Section: Introductionmentioning
confidence: 99%